2006
DOI: 10.1139/t06-037
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-controlled cavity expansion in clay

Abstract: Experimental studies and numerical simulation of experiments were conducted on pressure-controlled cavity expansion in clay. The modified Cam-clay model was used to describe the clay behaviour. The experimental data are in good agreement with the simulation results, indicating that the adopted numerical simulation procedure is a plausible and reliable technique to study the fundamental behaviour of pressure-controlled cavity expansion. A new parameter, cavity aspect ratio (CAR), was defined to better describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The measured fracturing pressure of approximately 300 kPa is approximately 9 times the undrained shear strength, i.e., 34 kPa. The result is consistent with the theoretical ultimate cavity expansion pressure in soil (Au et al 2006). However, the magnitude of fracturing pressure is dependent on injection rate and overconsolidation ratio of the soil (Mori and Tamura 1987;Au 2001;Soga et al 2003), as shown in Fig.…”
supporting
confidence: 90%
“…The measured fracturing pressure of approximately 300 kPa is approximately 9 times the undrained shear strength, i.e., 34 kPa. The result is consistent with the theoretical ultimate cavity expansion pressure in soil (Au et al 2006). However, the magnitude of fracturing pressure is dependent on injection rate and overconsolidation ratio of the soil (Mori and Tamura 1987;Au 2001;Soga et al 2003), as shown in Fig.…”
supporting
confidence: 90%
“…The two problems (i.e., pressure-controlled and displacement-controlled) have various applications in geotechnical engineering problems. For instance, pressuremeter tests (PMTs) and compaction grouting are pressure-controlled problems (Au et al 29 ). However, the displacement-controlled cavity expansion problem is more appropriate for interpreting the penetration problems of cone penetrometers, driven piles, PVDs, flat dilatometers (DMTs), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show that particle shape has a significant influence on properties of engineering interest for granular soils (Chang et al, 2018;Cho et al, 2006a;Holubec and D'Appolonia, 1973;Liu and Lehane, 2013;Santamarina and Cho, 2004;Vaid et al, 1985;Yang and Luo, 2015). To incorporate this knowledge into geotechnical practice it is necessary to measure shape.…”
Section: Introductionmentioning
confidence: 99%